Pre-stress performance in an instrumental training predicts post-stress behavioral alterations in chronically stressed rats - Iguchi, Yoshio; Kosugi, Sakurako; Lin, Ziqiao; Nishikawa, Hiromi; Minabe, Yoshio; Toda, Shigenobu (Frontiers in Behavioral Neuroscience, 2015)
Stress is a major factor in the development of major depressive disorder (MDD), but few studies have assessed individual risk based on pre-stress traits. In this study, we employed appetitive instrumental lever pressing with a progressive ratio schedule to assess the individual pre-stress behavioral and cognitive traits in experimentally naïve Sprague–Dawley rats. Based on the behavioral data, the animals were classified into four subgroups (Low Motivation, Quick Learner, Slow Learner, and Hypermotivation), and exposed to chronic unpredictable stress (CUS) before monitoring their post-stress responses once each week for 4 weeks to identify early- and late-appearing CUS-induced behavioral phenotypes. The four subgroups exhibited different behavioral phenotypes after CUS. Therefore, we identified distinct relationships between pre-stress traits and the post-stress phenotypes in each subgroup. In addition, many of the CUS-induced phenotypes in rats corresponded to symptoms in human MDD or they had putative relationships with them. We concluded that the consequences of stress may be predicted before stress exposure by determining the pre-stress traits of each individual.